Analysis of the Basic Abilities of Grade V Students in Working on Volume of Space Building Problems - Witdanarko, Fajar; Wiryanto, Wiryanto; Mariana, Neni (IKIP Widya Darma Surabaya, 2024)
Objectives: The purpose of this simple research is to find out the following: 1) the essential ability of grade V elementary school students in working on problems about the volume of space, especially cubes and beams; 2) the difficulties faced by students in solving volume problems of cubes and beams. Method: The research method used in this simple research is a qualitative description with data collection techniques using written tests. The subjects of this study amounted to 5 students consisting of 2 female students and three male students from grade V elementary school. Results: The results showed that the essential ability of grade V elementary school students in working on problems about the volume of space buildings, especially cubes and beams, obtained an average score of 30. Students in grade V elementary school have difficulty working on volume problems of cubes and beams in the form of story problems; this is evidenced by the answers to the test instrument questions in the form of story problems, which all get the result 0. Novelty: The novelty in this study lies in identifying what mistakes are often made by fifth-grade students in working on volume problems of building space. These errors are grouped into several categories: reading, understanding, processing data, and writing answers. This allows teachers to target more specific interventions based on the types of errors made by students.